Works - Laud, William (The Library of Anglo-Catholic Theology)
Vol. 1. Sermons.- Vol. 2. Conferences with Fisher.- Vol. 3. Devotions, diary and history.- Vol. 4. History of troubles and trial.- Vol. 5. pt. 1. History of his chancellorship.- Vol. 5. pt. 2. Accounts of province.- Vol. 6. pt 1. Miscellaneous papers; Letters.- Vol. 6. pt 2. Letters; Notes on Bellarmine.- Vol. 7. Letters.